Public health practitioners' views of the 'Making Every Contact Count' initiative and standards for its evaluation. (30th May 2018) - Chisholm, A; Ang-Chen, P; Peters, S; Hart, J; Beenstock, J
Abstract: Background: National Health Service England encourages staff to use everyday interactions with patients to discuss healthy lifestyle changes as part of the 'Making Every Contact Count' (MECC) approach. Although healthcare, government and public health organisations are now expected to adopt this approach, evidence is lacking about how MECC is currently implemented in practice. This study explored the views and experiences of those involved in designing, delivering and evaluating MECC. Methods: We conducted a qualitative study using semi-structured interviews with 13 public health practitioners with a range of roles in implementing MECC across England. Interviews were conducted via telephone, transcribed verbatim and analysed using an inductive thematic approach. Results: Four key themes emerged identifying factors accounting for variations in MECC implementation: (i) 'design, quality and breadth of training', (ii) 'outcomes attended to and measured', (iii) 'engagement levels of trainees and trainers' and (iv) 'system-level influences'. Conclusions: MECC is considered a valuable public health approach but because organisations interpret MECC differently, staff training varies in nature. Practitioners believe that implementation can be improved, and an evidence-base underpinning MECC developed, by sharing experiences more widely, introducing standardization to staff training and finding better methods for assessing meaningful outcomes.